2023
DOI: 10.1111/jgs.18223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of fall risk in older adults who use lower‐limb prostheses: A scoping review

Abstract: Background No reviews or evidence‐based clinical protocols exist to evaluate fall risk in older adults who use lower‐limb prostheses, despite falls being prevalent and costly in this population. This scoping review sought to determine assessments, defined as clinical outcome measures and gait parameters, associated with fall risk in this population to determine if a systematic review is warranted and help inform an evidence‐based clinical protocol. Methods Google Scholar, PubMed, and Scopus were searched on Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…However, current billing practices in prosthetics dictate that any follow-up care is bundled into a lump-sum payment for the device, and providers are not reimbursed for follow-up care outside of this base rate. Additionally, people who are older adults, belong to systematically marginalized groups, or live in rural communities are often underrepresented in prosthetics literature (57)(58)(59), including technology development. To elucidate health disparities, researchers must first collect and report detailed socioeconomic information, as a recent review determined 84% of the 420 manuscripts reviewed did not report race or ethnicity of the participants (60).…”
Section: Promote Health Equitymentioning
confidence: 99%
“…However, current billing practices in prosthetics dictate that any follow-up care is bundled into a lump-sum payment for the device, and providers are not reimbursed for follow-up care outside of this base rate. Additionally, people who are older adults, belong to systematically marginalized groups, or live in rural communities are often underrepresented in prosthetics literature (57)(58)(59), including technology development. To elucidate health disparities, researchers must first collect and report detailed socioeconomic information, as a recent review determined 84% of the 420 manuscripts reviewed did not report race or ethnicity of the participants (60).…”
Section: Promote Health Equitymentioning
confidence: 99%
“…More than half of DRFs are caused by a fall, which often occurs while walking; therefore, several studies have indicated that changes in gait patterns are related to falls [ 7 , 8 ]. Quantitative gait parameters such as slower gait speed, shorter stride length [ 9 ], and foot kinematics such as lower peak dorsiflexion angle of the foot [ 10 , 11 ], as well as larger variability of these parameters [ 12 ], have been reported to be associated with fall risk [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%